EFFECT OF THE EXTENT OF MEDIASTINAL LYMPHODISSECTION ON THE RESULTS OF COMBINED MODALITY TREATMENT FOR STAGE IIIA (N2 ) NON-SMALL CELL LUNG CANCER - E. O. Mantsyrev; A. V. Vazhenin; O. A. Gladkov; A. A. Lukin; M. N. Mironchenko; Ya. A. Gnatyuk; S. N. Timofeev (Сибирский онкологический журнал, 2016)
Short-and long-term results of combined modality treatment with systematic (n=60) and selective (n=51) mediastinal lymphodissection were compared in 111 patients with IIIA(N2 ) stage non-small lung cancer taking into account the tumor site, histological pattern of the tumor and the extent of radical surgery. The recurrence-free survival rate was significantly higher in patients with squamous cell lung cancer who underwent systematic lymphodissection than in patients who underwent selective lymphodissection. The median disease progression-free survival was 31 months and 14.5 months and the overall 5-year survival rates were 43,4 % and 16 %, respectively (p<0,05). A significant increase in recurrence-free and overall 5-year survival rates was observed in group I patients with cancer of the left lung as compared to that observed in group II patients. Selective mediastinal lymphodissection may be the operation of choice in patients with stage IIIA(N2 ) non-small cell lung cancer and in patients with cancer of the right lung who received combined modality treatment including adjuvant radiation therapy.